2022
DOI: 10.1371/journal.pone.0273071
|View full text |Cite
|
Sign up to set email alerts
|

A double whammy: The association between comorbidities and severe dengue among adult patients—A matched case-control study

Abstract: Background Dengue infection is the most prevalent mosquito-borne viral infection globally. Concurrently, there has also been an upsurge of non-communicable comorbidities. We aimed to investigate the association between these comorbidities and the development of severe dengue. Methods We performed a retrospective, case-control study involving 117 cases with severe dengue and 351 controls with non-severe dengue; matched according to gender, age (+/- 5 years old), and admission date (+/- 2 weeks). We analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In total, 1700 studies were retrieved from the database in the initial search, of which 278 were considered potentially eligible after reviewing the titles and abstracts. After reading the full text of the articles, 31 articles were eligible, of which 4 studies used the same dataset as the others, and 27 articles were included in this meta-analysis [15,20,[25][26][27][28][29][30][31][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The processes of study screening are shown in Fig 1, and the general characteristics of the included studies and the corresponding NOS scores are shown in Tables 1 and 2.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In total, 1700 studies were retrieved from the database in the initial search, of which 278 were considered potentially eligible after reviewing the titles and abstracts. After reading the full text of the articles, 31 articles were eligible, of which 4 studies used the same dataset as the others, and 27 articles were included in this meta-analysis [15,20,[25][26][27][28][29][30][31][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The processes of study screening are shown in Fig 1, and the general characteristics of the included studies and the corresponding NOS scores are shown in Tables 1 and 2.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Vector control through the movement to keep the environment clean by involving all family members has proven effective in preventing dengue endemic (20). Older adults who tend to have comorbidities, such as hypertension, heart disease, and diabetes, must be monitored by their families because they are more susceptible to the dengue virus (21). In the elderly, the dengue fatality rate is higher due to comorbidities, even without considering the severity of the fever (22).…”
Section: Introductionmentioning
confidence: 99%